2013
DOI: 10.1080/01635581.2013.776693
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Antıneoplastic Actions of Caffeic Acid Phenethyl Ester (CAPE): Therapeutic Perspectives

Abstract: Cancer prevention and treatment strategies have attracted increasing interest. Caffeic acid phenethyl ester (CAPE), an active component of propolis extract, specifically inhibits NF-κB at μM concentrations and shows ability to stop 5-lipoxygenase-catalyzed oxygenation of linoleic acid and arachidonic acid. Previous studies have demonstrated that CAPE exhibits antioxidant, antiinflammatory, antiproliferative, cytostatic, antiviral, antibacterial, antifungal, and, most improtantly, antineoplastic properties. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 77 publications
0
57
0
1
Order By: Relevance
“…Caffeic acid phenyl ester (CAPE) is one of the main medicinal components of honeybee propolis that possesses a variety of biological and pharmacological actions such as potent free radical scavenging, antioxidant, anti-inflammatory, cytoprotective, immunomodulatory, and antiviral and promising anticancer properties [1]. Also, the ameliorating and counteracting effects of CAPE on different disease modalities of hematological, blood coagulation, and vascular abnormalities have recently been emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic acid phenyl ester (CAPE) is one of the main medicinal components of honeybee propolis that possesses a variety of biological and pharmacological actions such as potent free radical scavenging, antioxidant, anti-inflammatory, cytoprotective, immunomodulatory, and antiviral and promising anticancer properties [1]. Also, the ameliorating and counteracting effects of CAPE on different disease modalities of hematological, blood coagulation, and vascular abnormalities have recently been emerged.…”
Section: Introductionmentioning
confidence: 99%
“…CAPE acts to downregulate inflammation by blocking NF-κB, and affects a variety of mediators, including adhesion molecules, cytokines and iNOS. CAPE is a well-documented inhibitor of NF-κB, which may be an action mechanism for the CAPE-mediated anti-inflammatory and anticancer effects (4,38). Although CAPE has been described to conduct its anti-inflammatory activities by modulating different inflammatory pathways, including inhibition of the transcription factors NF-κB and signal transducer and activator of transcription 3 (acute-phase response factor), the compound has already been evaluated for antitumor efficacy in numerous in vitro and in vivo studies (39,40).…”
Section: Anti-inflammatory Effects Of Capementioning
confidence: 99%
“…1). It has been shown that this active component of propolis possesses anti-inflammatory, immunomodulatory, antineoplastic, antioxidant and wound-healing properties (1)(2)(3)(4). Inflammation is induced by the release of chemical mediators from damaged tissue and migratory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, it was found that CAPE has time- and dose-dependent cytotoxic effects on CCRF-CEM leukemic cells [17]. The major molecular fundamentals of cytotoxic effects of CAPE in terms of protein kinases, antiapoptotic and apoptotic proteins, growth factor pathways, transcription factors, cell cycle proteins, cell adhesion molecules, metastasis, and some others have extensively been reviewed by Akyol et al [18]. …”
Section: Introductionmentioning
confidence: 99%